Analisis Statistik Deskriptif Nilai UAS Ekonomitrika Mahasiswa dengan Program SPSS 23 & Eviews 8.1 - Maswar Maswar (Program Pascasarjana Universitas Ibrahimy, 2017)
One of the simplest analysis and often used as a preliminary analysis of the quantitative research is descriptive statistical analysis. This analysis aims to describe the results of the calculation of numerical data. Some descriptive statistical analysis techniques that are commonly used include: 1) The presentation of data in tables or histograms, 2) The central tendencyof data, 3) The dispersion of data, and 4) The distribution of data. In the analysis of UAS Ekonomitrika with SPSS 23 and Eviews 8.1, found differences in the operational steps in each of these programs. The output of SPSS 23 displays histogram curve is accompanied with normality, explained the value of the variance, standarderror of the mean, standard error of skewness, and kurtosis , but in Eviews 8.1 not display case. In contrast, in Eviews 8.1 displays the value of the JB, the probability JB, sum.square deviation value while in SPSS 23 is not so. The equation of the output that is displayed on the two programs, namely: 1) Displays the number of observational data is processed, 2) Showing mean, median, mode, sum, minimum, maximum, skewness and kurtosis, and 3) Present Histogram.